PENINGKATAN PRODUKTIVITAS MASYARAKAT DESA KEDUNGPELUK KECAMATAN CANDI SIDOARJO MELALUI PEMASANGAN PJU (PENERANGAN JALAN UMUM) - Suparto Suparto; Evi Yuliawati; Yoniv Erdianto; Lukmandono Lukmandono; Indung Sudarsono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Bangoan sub-village, Kedunglukan Village, Candi Sidoarjo District, is a village with potential natural resources in ponds and goat farms and a hardworking, tenacious and creative community. However, the community has limitations in business due to the absence of lighting on public roads, which results in the lack of investors willing to invest in a company, limited working hours or business operations, potential for crime, frequent minor accidents, limited health services such as childbirth, etc. Through this community service program, Public Street Lighting (PJU) was installed. The method is carried out by conducting surveys and coordinating with village officials and PLN, determining installation points, installation, maintenance training, and entrepreneurship training. With the installation of these lightings, the community is very enthusiastic about developing a side business at night after completing their routine at work, such as making petis, shrimp paste, smoking fish, packaging, etc. In addition, both general and religious educational activities are also seen to be active with learning to recite the Koran after sunset, group study, and night patrols so that overall, it can improve the quality of the people Kedungluk village.Keywords: training, lights, lighting